Improving the Learning Outcomes of Grade IX Students on the Material of Faith in the Last Day through the Application of Audio Visual Media at SMP Negeri 1 Setia - Marwani (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to improve the learning outcomes of grade IX students on the material of faith in the last day through the application of audio-visual media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using a qualitative approach. Data collection was carried out through learning outcome tests, observations, and interviews. Each cycle includes the stages of planning, implementation, observation, and reflection. The results showed that there was a significant increase in student learning outcomes. The average class score increased from 65 in the pre-action to 72 in the first cycle and 80 in the second cycle. In addition, the percentage of students who achieved scores above the Minimum Completion Criteria increased from 30% in the pre-action to 55% in the first cycle and 85% in the second cycle. The results of observations and interviews showed that students were more active, motivated, and involved in discussions when audiovisual media were used. They found it easier to understand abstract concepts and showed an increase in critical thinking skills.